Early internationalizing firms in the Brazilian software industry - Pilwarsch, Philip (2017)
This paper tries to understand the factors that influence Brazilian software firms to pursue an accelerated internationalization strategy. A literature review gives an overview of existing theories trying to explain the born global phenomenon. Based on these theories a framework was developed, which lists the factors that have an impact on early internationalization. The factors are grouped in three different categories: internal, external, and entrepreneur factors. During interviews with three Brazilian software international ventures the relevant factors were identified. The results show that the flexibility and client-followership are important internal factors. Niche markets and foreign competition are influencing the internationalization from the external side. International experience and informal networks are important entrepreneur factors. Moreover, a difference between business-to-business and business-to-consumer firms could be found.